MORPHOBIOLOGY AND BIOCHEMICAL VALUE OF LYCHEE PLANT (LITCHI CHINENSIS) - Rakhmatullaeva Roziya Shukhratovna (Journals Park Publishing, 2022)
This article provides valuable scientific information about the Chinese lychee plant (Litchi chinensis) in folk medicine, origin and distribution area, medicinal properties, and cultivation technology.
Keywords: heat-loving, calyx, calcium, phosphorus, stem.